Multi-Keyword Certificateless Searchable Public Key Authenticated Encryption Scheme Based on Blockchain - Yang, Xiaodong; Chen, Guilan; Wang, Meiding; Li, Ting; Wang, Caifen (IEEE access, 2020)
As a quite attractive secure search mechanism in cloud environments, searchable encryption allows encrypted files to be searched by keyword and does not reveal any information about original data files. However, most existing searchable encryption schemes only support single keyword ciphertext retrieval, and they cannot resist against inside keyword guessing attacks. Besides, the previous schemes rarely focus on integrity verification and fair transactions without any third party. Focusing on these problems, we propose a multi-keyword certificateless searchable public key authenticated encryption scheme based on blockchain. We use certificateless cryptosystem to encrypt keywords, which avoids the problems of certificate management in traditional cryptosystem and key escrow in identity-based cryptosystem. Our scheme also supports multi-keyword search, which locates encrypted files precisely and returns the desired files. Moreover, we upload the real encrypted files to the cloud server, while the encrypted indexes are put in blockchain, which ensures the anti-tampering, integrity and traceability of the encrypted indexes. The anti-tampering of blockchain also ensures that users can receive accurate search results without any third party verification. Furthermore, we utilize smart contract to track monetary rewards, which enables fair transactions between data owners and users without any trusted third party. We prove that the proposed scheme is secure against inside keyword guessing attacks in the random oracle model. Finally, our performance evaluation shows that the proposed scheme has higher computational performance than other related schemes.